PERLINDUNGAN HUKUM BAGI KONSUMEN BERKAITAN DENGAN PENCANTUMAN DISCLAIMER OLEH PELAKU USAHA DALAM SITUS INTERNET (WEBSITE) - Ni Putu Ria Dewi Marheni (University of Udayana, 2014)
This Research is entitled “Legal Protection for Consumers Related to the Inclusion of Disclaimer by Business Owner in Website”. The problems of the present study are: first, how the inclusion of disclaimer in websites in Indonesia is like; second, what the legal protection for consumers related to the inclusion of disclaimer by business owner in websites is like. The method used in the present study is the normative legal research. The results of the study showed: first, no norm regulating disclaimer in the Act Number 11 of 2008 concerning the electronic information and transaction which specifically regulate activities in the cyberspace. However, if generally viewed from the protection for consumers in the Act Number 8 of 1999 concerning Protection for Consumers, most inclusions of disclaimer in the website is classified as exoneration clausal which is partially prepared by business agents to avoid what they are supposed to be responsible for. Second, the form of legal protection needed by consumers in the internet is still weak. However, the general legal protection for consumers may be provided through: a) Being preventive: Reliability Certification Board ‘Lembaga Sertifikasi Keandalan’(LSK) which is supposed to give certification for every internet site already regulated by the Regulation of the Republic of Indonesia Number 82 of 2012 concerning the Implementation of Electronic System and Transaction which is a derivative of Article 10 clause (2) of the Act Number 11 of 2008 concerning Electronic Information and Transaction; b) being repressive: through Litigation Lane which may be done by submitting a civil suit and civil sanction based on the Act Number 11 of 2008 concerning Electronic Information and Transaction. Another alternative is through the Non Litigation lane, that is, the Arbitrate Lane, which is settled using the Alternative of Dispute Settlement